Generalized epilepsy and mild intellectual disability associated with 13q34 deletion: A potential role for SOX1 and ARHGEF7. (July 2018) - Orsini, A.; Bonuccelli, A.; Striano, P.; Azzara, A.; Costagliola, G.; Consolini, R.; Peroni, D.G.; Valetto, A.; Bertini, V.
Abstract: Terminal deletions of long arm of chromosome 13 are rare and poorly characterized by cytogenetic studies, making for difficult genotype-phenotype correlations. We report two siblings presenting generalized epilepsy, intellectual disability, and genitourinary tract defects. Array CGH detected a 1.3 Mb deletion at 13q34; it contains two protein-coding genes, SOX1 and ARHGEF7, whose haploinsufficiency can contribute to the epileptic phenotype.